Understanding Stress among Retirees of Higher Educational Institutions in Nigeria - N.S. Oguzor; H.E. Adebola; J.A. Opara (University of Sofia, 2011)
This study examines the effect of stress on retirees. The study also identifies the cause of stress and strategies for reducing stress on retirees. The population of the study comprised 4000 male and female retirees of a Nigerian institution of higher learning. The sample of the study was 400 selected from the institution using simple random sampling technique. A questionnaire was used for data collection. Data collected were analyzed applying frequency counts and mean statistic. Findings revealed that standing for a long time can cause stress for retirees. The finding of the study also revealed that non-payment of gratuity and pension can cause stress for retirees. The findings of the study further showed eight strategies for reducing stress. Based on the findings recommendations were made.